Brazilian Academic Capitalism and the Commodification of Raw Material Knowledge in the Crisis Scenario - de Paula, Alisson Slider do Nascimento (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
This research seeks to analyze the logic of Brazilian academic capitalism that conditions a process of commodification of the production of knowledge, as well as the prioritization of the supply of training courses for professionals. This process is characterized as raw material knowledge contributing to the creation of a kind of World Class University. Concerning the methodological procedures of the research, it was decided to develop a bibliographic and documentary research based on critical-dialectic epistemology. Content analysis was used in the treatment of data. It is considered that, despite policy development for the entrepreneurship of higher education through public-private partnerships that subsidize the expansion of the private-mercantile sector of higher education through its financialization, the adaptation to the standard of the New American University is carried out from the movement to commercialize scientific production and private investments in the public sector, as well as prioritizing the offer of technological courses and bachelor's degrees to the detriment of undergraduate degrees, in addition to the incorporation of technological innovations resulting from the pandemic crisis, thus tending toward the constitution of the World Class University.